The Role of the Binmas Unit in Counseling on the Prevention of Two-Wheeled Theft Crimes That Occur in the Legal Area of ​​the Cirebon Police - Ervindo Thio Prabowo (Tanggon Kosala, 2021)
The background of this study is that there are still cases of motorcycle theft found in the Cirebon Police Jurisdiction. Therefore, it is deemed necessary to conduct a study on the implementation of Cirebon Police Station Binmas unit’s role in preventing the criminal act of motorcycle theft in the Cirebon Police Jurisdiction. The research questions of this study are: (1) How is the description of the criminal act of motorcycle theft in the jurisdiction area of Cirebon Police Station?, (2) How is the implementation of Binmas unit’s role in preventing criminal act of motorcycle theft?, (3) What are the factors that influence the performance of the Binmas unit in Cirebon Police Station in preventing criminal act of motorcycle theft that occur in the Cirebon Police Jurisdiction? The theories of analysis in this study are the role theory (which functions to analyze the implementation of counseling conducted by the Binmas unit of Cirebon Police Station in preventing motorcycle theft), communication theory (which functions to analyze what factors that influence the performance of the Binmas unit), and the Binmas Unit concept that becomes the reference in this study. A qualitative approach with a field research method was used in this study. The focus of this study was to elucidate the implementation of counseling by the Binmas unit of the Cirebon Police Station in preventing the criminal act of motorcycle theft in the Cirebon Police Jurisdiction. Interviews, observation, and document analysis were used as a mean to collect the data in this study. The data analysis techniques included in this study were data condensation, data presentation and conclusion drawing. The results of this study indicate that the depiction of motorcycle theft in the Cirebon Police Jurisdiction has decreased in 2018 to 2019. However, motorcycle theft is still the most common crime compared to molestation and gambling. The main factors that still become the obstacles are the quality of members of Binmas unit of the Cirebon Police Station who have not yet received a vocational education, limited facilities and infrastructure as well as the lack of attention from the public in accepting the efforts made by the Binmas unit of the Cirebon Police Station in preventing the motorcycle theft crime.